Regulation of the dorsal morphogen by the Toll and torso signaling pathways: A receptor tyrosine kinase selectively masks transcriptional repression. - Rusch, J.; Levine, M. (Genes & Development, 1994)
The dorsal (dl) nuclear gradient initiates the differentiation of the mesoderm, neuroectoderm, and dorsal ectoderm by activating and repressing gene expression in the early Drosophila embryo. This gradient is organized by a Toll signaling pathway that shares many common features with the mammalian IL-1 cytokine pathway. Here we present evidence that a second signaling pathway, controlled by the torso (tor) receptor tyrosine kinase, also modulates dl activity. Evidence is presented that the tor pathway selectively masks the ability of dl to repress gene expression but has only a slight effect on activation. Intracellular kinases that are thought to function downstream of tor, such as D-raf and the rolled MAP kinase, mediate this selective block in repression. Normally, the Toll and tor pathways are both active only at the embryonic poles, and consequently, target genes (zen and dpp) that are repressed in middle body regions are expressed at these sites. Constitutive activation of the tor pathway causes severe embryonic defects, including disruptions in gastrulation and mesoderm differentiation, as a result of misregulation of dl target genes. These results suggest that RTK signaling pathways can control gene expression by antirepression, and that multiple pathways can fine-tune the activities of a single transcription factor.